A Genealogy of Identity: Reflections on post-1857 Islamic Political Thought in Colonial India. (January 2015) - Nasir, Muhammad Ali
There were various political discourses associated with the Islamic community in colonial India. These included trends that were later understood under the rubric of 'Muslim' nationalism and Indian nationalism, along with other critical stances that cannot be subsumed within either nationalism. This article explores one such trend: it reads genealogically the trajectories of concepts through which the problematic of Islamic political identity developed in the context of the post-1857 experience. In order to understand the way these arguments were formed the article analyses texts that both reflected on and were a reflection of socio-political dynamics. It concludes with a note on utilising such a genealogical approach in the study of trajectories in the development of political thought, and the possibilities of extending this approach to the sphere of entire cultures.